AESTHETIC PERCEPTION OF COLOUR IN TRAINING OF DESIGN STUDENTS - Kostiuk, Olha (The Modern Higher Education Review, 2023)
The article examines the aspects of colour training of design students, discusses the concept of colour competence and its importance in the process of professional training of future specialists in the field of design. The purpose of the article is to study the aesthetic perception of colour in the process of colour training of design students. Colour is highlighted as the most important element of aesthetic perception and emotional expression of design objects, has a psycho-emotional impact on the receiver (audience) and carries a certain informational value. The aesthetic perception of colour is understood as a complex process in which the awareness of aesthetic, artistic, and spiritual values takes place from the standpoint of sociocultural and historical factors. The need for colour competence through the study of a complex of professional disciplines is emphasised, which is decisive in the process of training design students. The study presents separate tasks using interactive technologies that contribute to the formation of aesthetic perception of colour in the process of colour training of students of higher education in the speciality 022.01 Design of the educational and professional programme “Graphic design” SI “Luhansk Taras Shevchenko National University”. It is noted that the development of colour competence of design students is an important prerequisite and indicator of their readiness for professional activity.